Reformasi Hukum Terhadap Budaya Penggunaan Hewan Sebagai Transportasi - Gaizka Ayu Satura; Amalia Putri Maharani; Herbin Marulak Siahaan (Jurnal USM Law Review)
This article aims to examine the gaps between regulations that negatively impact animal welfare, particularly regarding the legality of using animals as a means of transportation under Article 1, Point 9 of Law Number 22 of 2009 on Road Traffic and Transportation. The implementation of this regulation has led to exploitation resulting in violations of animal welfare, contradicting various animal protection laws. Adverse incidents involving horse-drawn carriages in different regions of Indonesia illustrate that animal welfare is often neglected in the practice of using animals for transportation. Therefore, regulatory reform is needed to align legislation with animal protection principles. This alignment must be addressed urgently because existing regulations fail to effectively protect animals, leading to the continuation of harmful practices. Without regulatory reform, animal exploitation in transportation will persist without adequate legal protection. The findings of this study reveal that using animals for transportation leads to exploitation and fails to ensure animal welfare protection, offering new insights based on progressive legal theory through regulatory reform. A regulatory reform that completely bans the use of animals for transportation, according to progressive legal theory, will provide a legal framework consistent with animal protection principles. This research stands out by integrating progressive legal theory to offer comprehensive solutions to address the impact of existing regulations while prioritizing animal welfare.